Enhanced performance for a high electrical conductive Mo2C electrode based proton ionic liquid electrolytes in supercapacitors. (11th July 2018) - Xu, Yan; Yang, Qing-Qing; Zhang, Wei-Bin; Liu, Mao-Cheng; Kong, Ling-Bin
Abstract: Carbides present high capacity due to their excellent conductivity as well as fast redox reactions with protons on the surface. Molybdenum carbide (Mo2 C), a typical carbide, has been synthesized successfully by calcining amine metal oxide. Served as electrodes for supercapacitors, the energy density is poor due to the narrow operating potential window in aqueous electrolyte (ca. 1.2 V). Whereas proton ionic liquids, a class of novel electrolyte, can expand the operating potential window as well as provide protons for electrochemical reactions, therefore guaranteeing a high energy density and capacitance. 1-ethyl-3-methylimidazolium acetate/acetonitrile (EMIMAc) is a new type proton ionic liquid for supercapacitors. For the Mo2 C electrode, the high specific capacitance of 88 F g −1 was achieved in 2 mol L −1 EMIMAc/AN electrolyte at a current density of 0.5 A g −1 . The Mo2 C//AC asymmetric capacitor with an operating voltage of 2.5 V retains 95% of the initial specific capacitance after 1200 cycles and exhibits a high energy density of 44.1 W h kg −1 . The prominent capacitive performance could be attributed to rapid electron transfer and highly exposed active sites of Mo2 C nanoflakes. Besides, 1-ethyl-3-methylimidazolium acetate ionic liquid provides wider electrochemical window to ensure large output. The use of EMIMAc/AN electrolyte dramatically improve the energy density of the asymmetric supercapacitors and can be applied to other carbides.